Application of Remote Sensing and GIS to Mass Wasting Susceptibility Mapping of the Akwapim South District - Toklo, E. (University of Ghana, 2024)
This thesis presents a comprehensive study on mass wasting susceptibility mapping in the Akwapim South District of the Eastern Region of Ghana. This study therefore used GIS-based multi-criteria decision analysis to model mass wasting susceptibility of the district by considering factors such as land use/land cover, slope, elevation, geology, soil depth and road distance. The study again investigated the causes, socio-economic and environmental impacts of mass wasting in the district. The study collected data from satellite images, google earth images, digital elevation models and field surveys for the mapping of the prone the prone areas. Factor weights were determined through the Analytical Hierarchy Process (AHP) and the factor class ratings were assigned through logical judgment. Mass susceptibility indices were determined based on a continuous numerical scale developed for this purpose by Saaty (1998) and the pairwise comparison matrix yielded a consistency ratio of 6.4% or 0.064, validating the robustness of the AHP method for this study. High and medium susceptibility zones were found to spread in 67.24 km2 and 56.03 km2 respectively in the study area while the low susceptible covers about 100.85 km2 of the total land area of the district. The study again revealed that various mass wasting types occur such as rockfall, rockslide, debris slide, landslide scars and soil creep occurs in the district. Furthermore, interviews and questionnaires were used to collect data for the social survey. The study unequivocally establishes that high elevation, weak rock formation and human-induced factors, notably poor construction practices and slope excavation for buildings are the principal drivers behind the mass wasting processes in the Akwapim South District, particularly in the Aburi enclave. Also, an in-depth analysis of the socio-economic and environmental impacts arising from mass wasting events in the study area has unearthed critical concerns. The far-reaching impacts encompass property damage, disruption of livelihoods and damage to the environment.
MPhil. Geography and Resource Development
Keywords: mapping; mass wasting susceptibility; Akwapim South District